Escherichia coli: a disease in the news through speeches of uncertainty and contradiction - Lopes, Felisbela (2013)
In May 2011 there was a rare outbreak of E. coli in Germany, and its origin was not clear. Through several weeks, official sources came forward with probable explanations that were contradicted by the following events. Through that time, media kept contradicting themselves, promoting uncertainty and making vegetables’ consumption decrease drastically. This article studies the Portuguese media coverage of this outbreak, looking into understanding the news coverage processes and also sources journalists talked to. Our study is based on news from Público, Jornal de Notícias and Expresso, three Portuguese newspapers with different editorial criteria and periodicity. Our corpus has 52 articles and there are 163 news sources quoted.